Research on multi-address time-based blockchain covert communication method - Dongyan HUANG; Kun LI (Tongxin xuebao)
Aiming at the problem of low amount of information carried by the existing block timestamp interval hiding method, a multi-address time-based blockchain covert communication method was proposed.Firstly, the ciphertext was split and transmitted by different addresses.The content of the ciphertext fragment was represented by the block timestamp interval of the address.Then the interval of the blocks was read and counted by the receiver where these addresses were located.Finally, the ciphertext was restored by combination.In addition, in view of the lack of concealment measures in the time-based blockchain covert communication system, a method of adjusting the time interval of transaction initiation was proposed to reduce the probability of address specificity caused by covert communication behavior.The experimental results verify that the transmission rate of the proposed method is about n times higher than that of the time-based blockchain covert communication method when n addresses are involved.